Introducing demographic corrections for the 10/36 Spatial Recall Test. (13th August 2015) - Gerstenecker, Adam; Martin, Roy; Marson, Daniel C.; Bashir, Khurram; Triebel, Kristen L.
Abstract : Objective: The 10/36 Spatial Recall Test is a measure of visuospatial memory and has been recommended for inclusion when administering a brief cognitive assessment to patients with multiple sclerosis by multiple groups. However, a notable limitation of the measure includes a lack of normative data with demographic corrections. Thus, the primary objective of the current study was to examine demographic influences on the 10/36 Spatial Recall Test and to introduce demographically corrected normative data for the instrument. Methods: Data were collected from 116 participants over the age of 50 years. All study participants were free of any neurologic disease or disorder and classified as cognitively intact by a consensus conference team that was comprised of neurologists and neuropsychologists. All study participants were administered a neuropsychological evaluation that included the 10/36 Spatial Recall Test Version A at the baseline visit. Results: 10/36 Spatial Recall Test scores were affected by age, education, and race. Gender effects were not observed. Given these effects, regression equations were used to correct for the effects of demographic variables. The z ‐scores obtained from these corrections were not significantly influenced by demographical variables. Conclusion: The demographic corrections introduced in this paper offer the possibility to enhance the clinical utility of the 10/36 Spatial Recall Test. Copyright © 2015 John Wiley & Sons, Ltd.